Negotiating the Sacred and the Profane: Paradigm Shifts in the Tarekat Shiddiqiyah toward Economic Empowerment in Jombang, Indonesia - Nilna Fauza (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
This study explores the shift in the spirituality of the Shiddiqiyah Order towards an economic empowerment paradigm in order to address modern Islamic issues. The Order is claimed to be a reflection of the decline of Islam because it only emphasizes spirituality, while neglecting worldly affairs. The order focuses only on religious and mystical rituals. They are passive towards social problems and changes. Therefore, this study reflects the spirituality of the Shiddiqiyah Order, which makes community empowerment a means to achieve perfection before God. This effort is referred to as a shift to negotiate the concept of ijtihad in the order. This is a qualitative study, with primary data taken from interviews with members of the Shiddiqiyah Order and several mursyids. The data was then analyzed using triangulation involving authentic sources. The findings show that the metaphysical shift to the profane realm (community empowerment) is a spiritual step towards achieving peace in worshiping God. This shift is based on three basic concepts of ijtihad, namely qiyas, istihsan, and istislah, which state that the existence of the order is to provide social peace through spirituality. This process is then called the negotiation of the spirituality of the order.